KARAKTER FISIS KULIT DOMBA SAMAK NABATI MENGGUNAKAN BAHAN PENYAMAK GAMBIR (UNCARIA GAMBIR) - Elis Nurbalia; Prasetyo Hermawan (Politeknik ATK Yogyakarta, 2018)
The purpose of this study is to determine the physical character of vegetable tanned sheep using gambir (uncaria gambir). Twelve pieces of sheep pikel skin were tanned using 25% vegetable tanning material from three types of gambir (A, B, C) and two kinds of tanning formulations ((Std) and (Std + Aux)). Skin products were tested for physical characteristics (tensile strength, elongation, tear strength, softness and shrinkage temperature). Furthermore the test results were compared with two standard leather products, namely; standard 1 (SNI 06-0237-1989: standard for lining leather) and standard 2 (SNI 4593: 2011: standard for jacket leather). The use of all types of gambir and tanning formulations has produced skin that pass the standards of skin tensile strength, standard 1 (minimum 75 kg / cm2) and standard 2 (minimum 150 kg / cm2). The results of the skin elongation test showed that only the use of gambier A pass the standard 1 (maximum 25%) and only the use of gambier C with tanning formulations (Std + Aux) that did not pass standard 2 (maximum 60%). The results of the use of gambir A produced the highest tensile / elongation ratio, 12.16 kg / cm2for the tanning formulation (Std) and 10.42 kg/cm2for the formulation (Std + Aux). Skin tear strength was not required by standard 1 and all skins pass standard 2 (minimum 12.5 kg / cm). Skin softness was not required by standard 1 and all skins do not pass standard 2 standards (5.0-7.6 mm). The use of gambier B results the highest temperature shrinkage of skin, this was influenced by a high ratio t/nt (1.77) and low gum content (6.15%), the addition of auxiliaries (penetrator and sulphate oil) in the formulation tanning (Std + Aux) increases shrinkage temperature the skin from 760C to 780C.